Determinants of rapid weight gain in a cohort of children in the first six months of life - Maíra Barros Louro Menezes; Cristina Maria Mendes Resende; Danielle Fernandes Durso; Mariane Alves Silva; Jacqueline Isaura Alvarez Leite; Sarah Aparecida Vieira Ribeiro; Juliana Farias de Novaes; Sylvia Do Carmo Castro Franceschini; Maria Tereza Cartaxo Muniz; Gustavo Velasquez-Melendez (Jornal de Pediatria, 2025)
Objective: To evaluate the influence of genetic, gestational, birth, and socioeconomic factors on Rapid Weight Gain (RWG) in children between birth and six months. Methods: This is a cohort study with 267 children, information on individual and sociodemographics was obtained from the medical record. RWG was identified when the z-score difference in weight-for-age between two child assessments was > +0.67. The rs9939609 was assessed by Real-Time Polymerase Chain Reaction Taqman. The exploratory analysis of the cumulative incidence rate curves of RWG used the Kaplan-Meier, as well as the Log-Rank test to perform comparisons between the groups. To estimate the hazard ratio, the Cox semi-parametric model was used, to verify the quality of the fit of the proposed model the generalized Cox-Snell residuals were used. Results: The RWG between birth and six months was 31.84% and the incidence rate was estimated to be 2.31 cases/1000 person-days. The children who were born with inadequate weight or low weight had 1.88 times the risk of having RWG between birth and six months. In multivariate analysis, a higher risk of RWG in the first six months of life was found for children who were born weighing < 3000 g and whose mothers were overweight/obese in the pregestational phase, adjusted for the variables sex, rs 9939,609 and paternal education, rs9939609 was not associated with RWG. Conclusions: Children with lower birth weight and with mothers overweight/obese before pregnancy presented a higher risk of RWG in the first six months and rs 9939,609 was not associated with RWG.